Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Student Team Achievement Division (STAD) Pada Pembelajaran Tematik Terpadu di Kelas V - Annisa Al Khudry; Mai Sri Lena; Ari Suriani (Elementary Teacher Education Program, Majalengka University, 2023)
This research is motivated by the low learning outcomes of students, where more than half of the students get lower learning outcomes than the Minimum Learning Completeness (KBM) that has been set. Low learning outcomes are caused by a monotonous learning process, lack of innovation in learning media and models, and teacher-centered learning. To get more optimal learning outcomes, a cooperative learning model of Student Team Achievement Division type is used which is group-based, student-centered and trains students' critical thinking. This study aims to describe the use of cooperative learning model type Student Team Achievement Division in improving the learning outcomes of fifth grade students. This research is a class action research consisting of two cycles. Cycle I consisted of 2 meetings and cycle II consisted of 1 meeting. The data obtained were analyzed by quantitative and qualitative analysis. In the lesson plan assessment, there was an increase from 82.95% in cycle I to 93.18% in cycle II. In teacher activities and learner activities in cycle I, the results were 82.82% and 81.25% respectively and became 93.75% and 93.75% in cycle II. In cycle I, students' learning outcomes in integrated thematic learning obtained a score of 72.82 and became 83.22 in cycle II.